Предмет: Математика,
автор: опор1
решить уравнение(х-6)(х-6)+7х-х2=-8
пожалуйста
Ответы
Автор ответа:
0
(х-6)(х-6)+7х-2х=8
(х-6)(х-6)+9х=8
(х-6)(х-6)= 8*9=72х
(х-6)(х-6)=72х
2х-0=72х
2х=72х+0
2х=72х
х=72х:2
х=36х
Сделала как знаю(((
(х-6)(х-6)+9х=8
(х-6)(х-6)= 8*9=72х
(х-6)(х-6)=72х
2х-0=72х
2х=72х+0
2х=72х
х=72х:2
х=36х
Сделала как знаю(((
Автор ответа:
0
(х-6)(х-6)+7х-х2=-8
х2-6х-6х+36+7х-х2=-8
-5х=-36-8
-5х=-44
х=-44:(-5)
х=8,8
х2-6х-6х+36+7х-х2=-8
-5х=-36-8
-5х=-44
х=-44:(-5)
х=8,8
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: Аноним
Предмет: Физика,
автор: dazaypidr
Предмет: Обществознание,
автор: Madaspe